2019
DOI: 10.3389/fpls.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Somatic Embryogenesis of Japanese Pines

Abstract: Somatic embryogenesis (SE) in not only one of the most promising techniques for mass propagation of selected trees, but also is a valuable tool for basic research studies in cell biology and genetic engineering, and it allows the long-term ex situ conservation of genetic resources by cryopreservation techniques. This review reports the most recent progress in SE, protoplast culture, and cryopreservation of four important Japanese pines (Pinus thunbergii, Pinus densiflora, Pinus armandii var. amamiana, and Pinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 142 publications
(260 reference statements)
2
27
0
Order By: Relevance
“…Somatic embryogenesis (SE) is currently the most efficient technique for large-scale propagation in clonal forestry and a powerful tool for plant regeneration in basic biological studies, genetic engineering, and implementation of multi-varietal forestry [ 1 , 2 , 3 ]. However, a low SE initiation rate is one of the major problems in using SE in some species and among individuals and families within the same species [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic embryogenesis (SE) is currently the most efficient technique for large-scale propagation in clonal forestry and a powerful tool for plant regeneration in basic biological studies, genetic engineering, and implementation of multi-varietal forestry [ 1 , 2 , 3 ]. However, a low SE initiation rate is one of the major problems in using SE in some species and among individuals and families within the same species [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEG is one of the most popular osmoticants used in SE and reported to be an effective osmoregulator that plays an important role in enhancing embryo maturation efficiency in many conifers [ 5 , 11 , 29 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In this study, it was clearly demonstrated that, for C. japonica , the addition of PEG to the medium notably improved the embryo maturation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The low efficiency of somatic embryo maturation is one of the major problems hampering efficient mass production and limiting practical applications [ 4 ]. Therefore, the high-quality somatic embryo production is one of the most important factors for using SE protocols in commercial propagation and breeding programs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to studies of somatic embryo maturation of Picea abies , in which PEG is reported to stimulate embryogenesis but inhibit the subsequent germination process [ 72 ]. Partial desiccation and/or cold treatments after maturation on medium containing PEG have been reported necessary to improve somatic embryo germination and conversion in a number of conifer species, including some pines [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ], spruces [ 80 , 81 , 82 , 83 ], hybrid larch [ 84 ], Fraser fir [ 66 ], and Chinese fir [ 85 ].…”
Section: Resultsmentioning
confidence: 99%